The laws of medicinal advertisement: a comparative study between Malaysia and Australia / Nur Fayizah Mohd Abdun Nasser … [et al.] - Haron, Maisara; Muhammad, Zulliana; Ahmad Sodikin, Nur Sakinah; Mohd Abdun Nasser, Nur Fayizah (Faculty of Law, 2013)
This research has been conducted to analyse the existing legal framework in Malaysia governing the medicinal advertisement. The inadequacies in Medicines (Advertisement & Sale) Act 1956 are highlighted. The Act consists of various lacunae as compared to Medicines Australia Code of Conduct 17 Edition. Our concern is on how deceptive advertisements affect public at large. Any information which appears on the medicinal advertisement must be reliable to prevent negative consequences to the consumers. Basically, the Medicines Australia Code of Conduct 17 Edition is more comprehensive compared to Medicine (Advertisement & Sale) Act 1956 in many aspects. Hence, we have discussed each aspect that need to be improved and suggested some Recommendations